THE USE OF ENGLISH MEDIUM INSTRUCTION IN MULTILINGUAL CLASSROOMS IN JAPANESE LANGUAGE TEACHING - Olha Luchenko; Olha Doronina; Yevhen Chervinko (Novìtnâ Osvìta, 2024)
Purpose. This article examines the use of English medium instruction (EMI) for teaching Japanese as a foreign language (JFL) by non-native speakers with a focus on multilingual classrooms. It also explores teachers’ positive and negative beliefs about using EMI in classroom settings for JFL instruction. Methods and procedure. 274 non-native Japanese language teachers from around the world (57 countries) voluntarily participated in a survey, answering a questionnaire on Google Forms and Jotform. Both qualitative and quantitative methods were employed. The research instrument was piloted before the main study and was found to be effective and adequate to elicit the desired data. The research questions aimed to identify whether there were any relationships between the use of EMI and the multilingual classroom. Findings. The results showed a clear correlation between the extensive use of EMI and the multilingual character of JFL classrooms. Translanguaging turned out to be a common practice adopted by non-native Japanese teachers regardless of the primary language of instruction. The article concludes that EMI can be a valuable tool for JFL instruction in multilingual classrooms. Based on the investigation of the teachers’ beliefs, the results showed a changing positive attitude towards English employed in JFL classrooms. Implications for research and practice. The findings can be used to further investigate EMI in JFL instructional practices in multilingual classrooms, improve the quality of JFL instruction and facilitate the integration of multilingual education into foreign language teaching. Future research can explore the effectiveness of EMI in different JFL contexts and investigate the impact of EMI on students’ language learning outcomes.